Kontribusi Power Otot Kontribusi Power Otot Lengan terhadapat Hasil Lempar Cakram Siswa Ekstrakurikuler SMA Negeri 1 Salo Kabupaten Kampar Siswa Ekstrakurikuler SMA Negeri 1 Salo Kabupaten Kampar - Ikhlas Sadikin (Inspiree)
The  purpose  of  the study. The purpose of this study was to determine the contribution of arm muscle power to the results of discus throwing at SMA Negeri 1 Salo, Kampar Regency.